Phenotypic plasticity of senescence in Daphnia under predation impact: no ageing acceleration when the perceived risk decreases with age. Issue 2 (5th February 2020) - Pietrzak, Barbara; Rabus, Max; Religa, Maciej; Laforsch, Christian; Dańko, Maciej J.
Abstract : Recognising the nature of the predation risk, and responding to it accurately, is crucial to fitness. Yet, even the most accurate adaptive responses to predation risk usually entail costs, both immediate and lifelong. Rooting in life-history theory, we hypothesize that an animal can perceive the nuances of prey size and age selectivity by the predator and modulate its life history accordingly. We test the prediction that—contrary to the faster or earlier senescence under predation risk that increases with prey size and age—under predation risk that decreases with prey size and age either no senescence acceleration or even its deceleration is to be observed. We use two species of indeterminate growers, small crustaceans of the genus Daphnia, Daphnia Pulex and Daphnia magna, as the model prey, and their respective gape-limited invertebrate predators, a dipteran, midge larva Chaoborus flavicans, and a notostracan, tadpole shrimp Triops cancriformis . We analyse age-specific survival, mortality and fertility rates, and find no senescence acceleration, as predicted. With this study, we complete the picture of the expected non-consumptive phenotypic effects of perceived predation pressure of different age-dependence patterns.